If x = 3 7 + 2 2 + 3 7 − 2 2 then it is a root of which of these expressions?
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Let a = 3 7 + 2 2 and b = 3 7 − 2 2 . Consider the following identity:
( a + b ) ( a 2 − a b + b 2 ) ( a + b ) ( ( a + b ) 2 − 3 a b ) x ( x 2 − 3 ( 3 ) ) ⟹ x 3 − 9 x = a 3 + b 3 = 7 + 2 2 + 7 − 2 2 = 1 4 = 1 4 Note that x = a + b and a b = 3 ( 7 + 2 2 ) ( 7 − 2 2 ) = 3
Therefore, the answer is x 3 − 9 x − 1 4 .
Problem Loading...
Note Loading...
Set Loading...
We can use the cubic formula and "work backwards." We know that the cubic equation x 3 − 3 p x + 2 q = 0 with positive discriminant D = q 2 − p 3 has the unique real solution x = 3 − q + D + 3 − q + D . Here, q = − 7 , D = 2 2 and p = 3 q 2 − D = 3 , and the answer is x 3 − 3 p x + 2 q = x 3 − 9 x − 1 4 .